Updated opinion of the Uterus Commission of the Gynecological Oncology Working Group (AGO) and the Gynecological Endoscopy Working Group (AGE) of the German Society of Gynecology and Obstetrics (DGGG) on the randomized study comparing minimally invasive with abdominal radical hysterectomy for early-stage cervical cancer (LACC) - Hillemanns, Peter; Brucker, Sara; Holthaus, Bernd; Kimmig, Rainer; Lampe, Bjoern; Runnebaum, Ingo B.; Ulrich, Uwe; Wallwiener, Markus; Fehm, Tanja; Tempfer, Clemens (Geburtshilfe und Frauenheilkunde, 2019)
In this opinion on the randomized study comparing minimally invasive with abdominal radical hysterectomy for early-stage cervical cancer (LACC), the Uterus Commission of the Gynecological Oncology Working Group (AGO) and the Gynecological Endoscopy Working Group (AGE) of the Germany Society of Gynecology and Obstetrics (DGGG) state that, based on their examination of the published data, patients with FIGO stage IA1 (with LVSI), IA2 or IB1 cervical cancer must be informed about the results of this LACC study prior to making a decision on the route for radical hysterectomy.
Gesehen am 05.06.2019